THE DEVELOPMENT OF E-COMICS MEDIA BASED ON THE VARK MODEL TO MEASURE THE UNDERSTANDING OF ELEMENTARY SCHOOL STUDENTS - Rizka Novi Irmaningrum; Oriza Zativalen; A.F Suryaning Ati MZ (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2023)
The purpose of this research is to develop digital-based thematic learning media, namely e-comics media for elementary school students. E-comics will be developed with the VARK (Visual, Auditory, Reading, Kinesthetic) learning model which displays illustrated stories with sound reflections and is related to students' reading and kinesthetic activities in using the media. Develop digital-based thematic learning media, namely e-comics media for elementary school students. E-comics will be developed with the VARK (Visual, Auditory, Reading, Kinesthetic) learning model which displays illustrated stories with sound reflections and is related to students' reading and kinesthetic activities in using the media. The e-comics media will discuss ethnic diversity material for fourth grade elementary school students. The results of the validity test above, conclude that the average e-comics media based on the vark model is 96%, which means that the media is valid. The application of media at SD Muhamammadiyah Lamongan resulted in an increase in cycles 1 and 2, so e-comic learning media could increase students' understanding. The response results of using e-comics media based on the vark model were easy to apply by teachers and students at partner schools of PGSD UM Lamongan.